Allele-specific recombinase polymerase amplification for real-time detection of sickle cell anaemia in low-resource settings: evaluation of an isothermal nucleic acid amplification test to detect the βS globin point mutation in paediatric patients - Mary Natoli, PhD; Megan Chang, BA; Kathryn Kundrod, PhD; Jackson Coole, BS; Gladstone Airewele, MD; Venée N Tubman, MD; Rebecca Richards-Kortum, PhD (Elsevier, 2021)
Background: Sickle cell anaemia is a common, life-threatening disorder caused by a point mutation in the β globin gene. The high cost and complexity of conventional diagnostic methods limit the scope and sustainability of newborn screening for sickle cell anaemia and other haemoglobin disorders in resource-limited areas. Although several point-of-care tests are commercially available, most are antibody-based tests, which cannot be used in patients who have recently received a blood transfusion. Additionally, very low levels of sickle haemoglobin (HbS) in premature babies and some newborns may cause errors in immunoassays. DNA analysis provides the most reliable approach to diagnose haemoglobin disorders. However, DNA analysis is not currently available at the point of care due to its cost and complexity. Here, we describe a rapid, low-cost nucleic acid test that uses real-time fluorescence to detect the point mutation encoding HbS in one round of isothermal recombinase polymerase amplification. Methods: Venous and capillary blood samples were obtained from healthy volunteers who were recruited by word of mouth. Venous blood samples from patients with varying genotypes seen in the Sickle Cell Disease Program at Texas Children's Hematology Center were collected and deidentified under IRB-approved exemption. Genotypes, as determined by qualitative isoelectric focusing combined with quantitative high performance liquid chromatography (HPLC) to confirm a diagnosis, were provided with the blood samples. The assay was evaluated with genomic DNA extracted from a set of blood samples of varying genotypes using the Axxin T8-ISO, a low-cost, field-deployable benchtop fluorimeter. Findings: The developed assay demonstrated 100% sensitivity for both the βA globin and βS globin alleles, and 94·7% and 97·1% specificity for the βA globin allele and βS globin allele, respectively (n=91). We also demonstrate a complete sample-to-answer workflow using a two-step lysis method and direct input of lysate into the allele-specific assay, and genotyping of blood samples in an open-source, custom built fluorimeter whose components cost less than US$850. Interpretation: This sample-to-answer nucleic acid test has the potential to be adapted to other disease-causing point mutations in genomic DNA. The technology described could streamline diagnosis in resource-limited settings of patients with sickle cell anaemia who have recently undergone a blood transfusion, with a comparable cost to protein-based tests. Funding: NIH K23-HL148548-01A1.